Relationship between hepatitis B DNA Viral load in the liver and it\'s histology in patient with chronic hepatitis B - Tahmineh Biazar; Yousef Yahyapour; Mohammad Reza Hasanjani Roushan; Ramazan Rajabnia; Mahmoud Sadegi; Hasan; Mohammad Ranaei; Masomeh Bayani (Caspian Journal of Internal Medicine, 2015)
Background: Serial measurement of  hepatitis B virus (HBV) DNA levels in the liver and its relation with liver damage and serum HBV DNA levels are guide to begin and/or end a treatment course. This study evaluated the relationship between liver hepatitis B DNA viral load with liver histology in patients with chronic hepatitis B (HBV).